2020
DOI: 10.26434/chemrxiv.12919190.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bifunctional Pt-IrO2 Catalysts for the Oxygen Evolution and Oxygen Reduction Reactions: Alloy Nanoparticles vs. Nanocomposite Catalysts

Abstract: <p>In the present study different concepts for the development of bifunctional oxygen reduction reaction / oxygen evolution reaction (ORR / OER) electrocatalysts are explored and compared. Bifunctional ORR / OER catalysts are often suggested to improve the stability during startup and shutdown of fuel cells. Furthermore, they are proposed for so-called unitized regenerative fuel cells (URFCs) that would allow a closed loop system to use and produce hydrogen on demand. We compare the electrocatalytic perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…As for the example of alloying Ir with noble metal, Pt is one of the most promising choices to be selected. Arenz and coworkers studied the OER performance of Ir and Pt co‐catalyst from the viewpoint of alloy nanoparticles vs. nanocomposites 184 . The result indicates that the PtIr alloy catalyst can deliver enhanced electrocatalytic property but it also faces the question that the increase of Ir leads to the additional Ir loss, which will influence the activity and stability of the whole catalyst.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%
“…As for the example of alloying Ir with noble metal, Pt is one of the most promising choices to be selected. Arenz and coworkers studied the OER performance of Ir and Pt co‐catalyst from the viewpoint of alloy nanoparticles vs. nanocomposites 184 . The result indicates that the PtIr alloy catalyst can deliver enhanced electrocatalytic property but it also faces the question that the increase of Ir leads to the additional Ir loss, which will influence the activity and stability of the whole catalyst.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%
“…51,52 For the preparation of the Pt NPs, a surfactantfree colloidal approach was applied, 53 which was outlined in our recent work. 33,34 Briefly, the same volumes of NaOH EG solution (400 mM) and H 2 PtCl 6 •6H 2 O EG solution (40 mM) were mixed and heated to 160 °C in a microwave reactor for 3 min to obtain colloidal Pt NPs in EG with a concentration of 3.90 g Pt L −1 . To support the Pt NPs onto carbon, the Pt colloid in EG was flocculated with 1 M HCl and centrifuged, whereafter the Pt NPs could be separated from the EG and re-dispersed in acetone (3.90 g Pt L −1 ).…”
Section: Synthesis Of Supported Pt/c and Pt + Xau/c Nanocomposite Cat...mentioning
confidence: 99%
“…30 However, Guay and co-authors reported a laser ablation method to prepare surfactant-free Pt−Au bimetallic catalysts, avoiding a surfactant-removal process, and the obtained Pt−Au mixed and Pt−Au alloyed nanoparticles are used for FAO study. 32 In the present study, we use our previously introduced nanocomposite concept 33,34 to prepare Pt + xAu/C bimetallic nanocomposites with tunable Pt to Au ratio. Surfactant-free, metallic Pt and Au nanoparticles serve as starting blocks.…”
Section: Introductionmentioning
confidence: 99%